2019
DOI: 10.1177/1758573219843617
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PROMIS Global-10 compared with legacy instruments in patients with shoulder instability

Abstract: Background Outcomes instruments are used to measure patients’ subjective assessment of health status. The Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10 was developed to be a concise yet comprehensive instrument that provides physical and mental health scores and an estimated EuroQol-5 Dimension (EQ-5D) score. Methods A total of 175 prospectively enrolled patients with shoulder instability completed the PROMIS Global-10, EQ-5D, American Shoulder and Elbow Surgeons (ASES), Single As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…23 To evaluate global health, we chose PROMIS-10 because of its relatively short length and strong correlation with legacy outcome measures in patients with upper extremity illness. 24,25
Figure 1.BRS questionnaire is shown with six questions and Likert-type answers choices. Note that the questions are framed such that the most resilient patient would alternate choices between “Strongly Agree” and “Strongly Disagree.” BRS, Brief Resilience Scale.
…”
Section: Methodsmentioning
confidence: 99%
“…23 To evaluate global health, we chose PROMIS-10 because of its relatively short length and strong correlation with legacy outcome measures in patients with upper extremity illness. 24,25
Figure 1.BRS questionnaire is shown with six questions and Likert-type answers choices. Note that the questions are framed such that the most resilient patient would alternate choices between “Strongly Agree” and “Strongly Disagree.” BRS, Brief Resilience Scale.
…”
Section: Methodsmentioning
confidence: 99%
“…PROMIS has been evaluated in other areas of medicine for its validity compared with extremity-specific PROMs. Suriani et al 37 correlated the PROMIS Global-10 with legacy shoulder PROMs including the American Shoulder and Elbow Surgeons (ASES) score, Single Assessment Numeric Evaluation (SANE), and Western Ontario Shoulder Instability Index (WOSI) in the assessment of 175 patients with shoulder instability. The PROMIS Global-10 was developed to be a comprehensive instrument for the evaluation of mental and physical health.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PROMIS Global-10 showed high correlation with ASES but poor correlation with the SANE and Western Ontario Shoulder Instability, suggesting it is an unreliable outcomes instrument in populations with shoulder instability. 18 For patients with shoulder arthritis, 2 studies have found the PROMIS Global-10 to perform poorly compared with the ASES, Single Assessment Numeric Evaluation, and Western Ontario Osteoarthritis of the Shoulder. As for those undergoing shoulder arthroplasty, additional studies are required to determine which PROMIS instrument is most responsive to longitudinal changes, although the PROMIS PF CAT has superior content and criterion validity compared with the PROMIS Global-10 and PROMIS UE CAT.…”
Section: Columbia University Medical Centermentioning
confidence: 99%
“…In particular, I would be concerned about the ability of the PROMIS Global-10 to deliver on evaluating patients with shoulder arthritis, 19 shoulder replacement, 20 and shoulder instability. 18 In this case, the PROMIS Global-10 instrument is a mirage in the eye of this stakeholder type, and I posit that the key opinion leader/subject matter expert for the national registry consider including both the PROMIS PF CAT and the PROMIS UE CAT for the aforementioned shoulder pathologies. If I am an orthopaedic surgeon who is concerned about the "end result," then I would want to use the PROMs that are the most responsive to change, valid, and reliable (i.e., exhibit robust psychometric properties), and most importantly have well-defined minimally clinical important difference and substantial clinical benefit thresholds.…”
Section: Columbia University Medical Centermentioning
confidence: 99%
See 1 more Smart Citation